Mechanism of mitochondrial permeability transition pore induction and damage in the pancreas: inhibition prevents acute pancreatitis by protecting production of ATP. Issue 8 (12th June 2015) - Mukherjee, Rajarshi; Mareninova, Olga A; Odinokova, Irina V; Huang, Wei; Murphy, John; Chvanov, Michael; Javed, Muhammad A; Wen, Li; Booth, David M; Cane, Matthew C; Awais, Muhammad; Gavillet, Bruno; et al.
Abstract : Objective: Acute pancreatitis is caused by toxins that induce acinar cell calcium overload, zymogen activation, cytokine release and cell death, yet is without specific drug therapy. Mitochondrial dysfunction has been implicated but the mechanism not established. Design: We investigated the mechanism of induction and consequences of the mitochondrial permeability transition pore (MPTP) in the pancreas using cell biological methods including confocal microscopy, patch clamp technology and multiple clinically representative disease models. Effects of genetic and pharmacological inhibition of the MPTP were examined in isolated murine and human pancreatic acinar cells, and in hyperstimulation, bile acid, alcoholic and choline-deficient, ethionine-supplemented acute pancreatitis. Results: MPTP opening was mediated by toxin-induced inositol trisphosphate and ryanodine receptor calcium channel release, and resulted in diminished ATP production, leading to impaired calcium clearance, defective autophagy, zymogen activation, cytokine production, phosphoglycerate mutase 5 activation and necrosis, which was prevented by intracellular ATP supplementation. When MPTP opening was inhibited genetically or pharmacologically, all biochemical, immunological and histopathological responses of acute pancreatitis in all four models were reduced or abolished. Conclusions: This work demonstrates the mechanism and consequences of MPTP opening to be fundamental to multiple forms of acute pancreatitis and validates the MPTP as a drug target for this disease.